EVALUASI ATAS PENERIMAAN PAJAK DAN RETRIBUSI PARKIR PADA DINAS PENDAPATAN DAERAH DAN DINAS PERHUBUNGAN KOTA PALEMBANG - Riqkiansyah Jerry; Ahmad Subeki; Arista Hakiki (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2013)
This study aims: 1) To find out the supervision in the management of parking collection on tax revenues and parking fees at the Regional Revenue Service and the Transportation Office of the City of Palembang, 2) To find out the obstacles faced by the Regional Revenue Service and the Transportation Office of Palembang City in increasing parking tax revenues and parking retribution in Palembang City. The results of this study indicate that the supervision of parking fees is carried out in two forms of supervision, namely direct supervision and indirect supervision. While supervision carried out at the Regional Revenue Service of Palembang City was two formed, namely supervision of parking tax payers and supervision of parking collectors. The obstacle faced by the Regional Revenue Service is not meeting taxpayers, taxpayers delaying tax payments. Whereas the Department of Transportation's obstacles are lack of supervision, the ability of parking operators who still need guidance and lack of parking support facilities. To increase parking tax and retribution, the author recommends that more improve coaching and training for employees so that they can improve its work performance, further enhances supervision both directly and indirectly.